Mapping Pesantren Cooperative Research in the 2020-2025 Range with a Systemic Literature Review Approach - Irfanullah (MONETARIUM: Journal of Economics Business and Management, 2025)
Pesantren is one of the Islamic education institution that has a role in spread of islam. in its development, pesantren not only play role in education but also in socioeconomics. One form of fulfilling this role is establishment of pesantren cooperatives. There are 30 scientific articles that publish in the range 2020-2024 that research pesantren cooperative. The researchers talk about several topics like legal review, business operation, pesantren development, community empowerment, product and service, and consumer behavior.  Most of the research publish in 2022 and 2024 and most of author and journals only publish one research. Based of findings, there are some recommendations in research like taking research outside java island, impact of cooperatives in financial literacy, financial assessment, verified finance, and reviewing consumer behavior from the prespective of religiosity